DEVELOPMENT AND CHARACTERIZATION OF ASPIRIN – SUCROSE COMPLEX FOR IMPROVED DRUG DELIVERY - SHANTHALA H. K.; SHREYAS HIRETHOTA; KIRTI JAIN; NAVEEN CHANDRA (International Journal of Pharma and Bio Sciences, 2016)
Many drugs fail to reach market due to their poor water solubility. This paper presents an approach to increase solubility of Aspirin in presence of sucrose as an excipient, is suitable for an immediate release formulations. To improve the solubility, hence the bioavailability, its complex with sucrose was prepared in aqueous Ethanol, Kinetic energy calculation, evaluation of dissolution and drug excipient interaction was done using scanning electron microscopy (SEM), FTIR spectra, X-ray diffraction, differential scanning calorimetry (DSC) and in vitro dissolution study. Aspirin-sucrose complex were found to be having rough surface in SEM. DSC, thermograms, XRD and FTIR confirmed the formation of the complex. The 1:1 proportion by weight of aspirin-sucrose resulted in formulation for quick release. It was concluded that the complex of aspirin in definite proportion by weight with sucrose may be of potential use for improving the solubility of aspirin and hence its bioavailability.